Design and fabrication of Microfluidic devices: MOSFET & Capacitor - Osman, R. A.; Esa, S. R.; Prabakaran, Poopalan (Institute of Electrical and Electronics Engineers (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org